IMPLEMENTASI KUALITAS DAN SIKAPKERJA TERHADAP KINERJA PEGAWAI DAN KEPUASAN PELAYANAN DI KANTOR KECAMATAN SUNGAI PINANG OGAN ILIR - Ellen Suminiarni; Yun Suprani; Muhammad Said (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
Many research results on the quality of service employees in government offices. Like the research conducted by Rukayat regarding the Quality of Public Service in the Field of Population Administration in Pasir Jambu District. The results of his research indicate that the quality of public services in the field of population administration in Pasirjambu District, namely the Public Service section, has not provided good service to the community. However, the community is satisfied with the service in terms of reliability, namely reliability in handling any public complaints.The results of the study of quality and work attitudes on service performance and satisfaction in Sungai Pinang Ogan Ilir District showed the results of the path coefficients between variables having an influence at medium intervals. This means that the quality of service in this office must be further improved. Employee performance in serving the community must be improved again.